Studying Chrysan’s Growth and Outcome on Planting Media’s Variation and Leave Manure - Yusuf, Zulfa Tsania; Suparto, Slamet Rohadi; Wiyantono, Wiyantono (International Journal Labs, 2022)
Chrysanthemum is a strategic floriculture commodity to be developed. The growth and production of flowers is influenced by many factors including growing media and fertilization. This study aims to examine the effect of variations in planting media and concentrations of foliar fertilizer on the growth and yield of chrysanthemum. The study was conducted in a Completely Randomized Block Design with three replications. Treatment of planting media consisted of cow manure: husk charcoal: bamboo leaf humus (1:1:1), cow manure: husk charcoal: cocopeat (1:1:1), and cow manure: husk charcoal. : wood sawdust compost (1:1:1). Treatment of foliar fertilizer concentrations consisted of control (0 g/l); 2 g/l; 4 g/l; and 6 g/l. The data obtained were analyzed using the F test, if there was a significant variation, then proceed with the DMRT test at ? 5%. The results showed that the planting media treatment of cow manure: husk charcoal: bamboo leaf humus, had a better effect than other media, indicated by the variables of plant height, crown diameter, stem diameter, number of branches, number of flowers, flower diameter, flower initiation time, flower coloring time, and harvest time. The application of foliar fertilizer with doses of 6 g/l, 4 g/l, and 2 g/l gave higher yields of flowers than the control. A good combination treatment for flower yields was found in the combination of cow manure: husk charcoal: bamboo leaf humus planting media and leaf fertilizer concentration of 4 g/l which produced the highest number of flowers, while for growth was the combination of cow manure : husk charcoal: bamboo leaf humus planting media and leaf fertilizer concentration 2 g/l; cow manure: husk charcoal: cocopeat and leaf fertilizer concentration of 4 g/l; as well as cow manure: husk charcoal: cocopeat and the concentration of foliar fertilizer 6 g/l which gave the higher number of leaves.